Electronic properties of single walled carbon nanotubes synthesized by laser ablation - Ncube, Siphephile (My University, 2014)
Current research in the field of nano-electronics is directed towards device miniaturization in order to find ways to increase the speed of electronic devices. The work presented in this dissertation is on the electronic transport properties of single walled carbon nanotube (SWNT) ropes synthesized by laser ablation. The measurements were performed on devices with different geometries; namely SWNT mats, metal incorporated (aligned individual and bundled) SWNTs and lastly on aligned pure SWNTs from low temperatures up to room temperature. The work was performed so as to gain an understanding on how best to utilize SWNTs in the semiconductor industry towards miniaturization. Such an understanding would ultimately highlight if SWNTs can be considered as a viable alternative to the current silicon-based technology, which seems to be approaching its physical limit. For a mat of SWNTs, 3D-Variable range hopping is the principal conduction mechanism from 2 K – 300 K. The magneto-resistance was found to be predominantly negative with a parabolic nature which converts to a linear nature as the temperature is increased. The negative MR is a consequence of quantum interference and the positive upturn is attributed to wave function shrinkage at low temperatures as described by the Efros-Shklovskii model. The hopping ranges of the electrons for a SWNT mat increases as the temperature decreases due to manifestation of quantum effects and reduced scattering. It was also found that metal incorporation does not alter the properties of the SWNT significantly. SWNT ropes aligned by di-electrophoresis across a 1 micron gap between gold micro-electrodes, exhibit Tomonaga-Luttinger liquid (TLL) like behaviour, within the 80 K – 300 K temperature range. The effects of confinement and electron-electron interaction unique to one dimension were identified in electronic transport as a non-universal power law dependence of the differential conductance on temperature and source-drain voltage. Ballistic conductance at room temperature was confirmed from the high frequency transport of the SWNT devices. The complex impedance showed some oscillatory behaviour in the frequency range 6 to 30 GHz, as has been predicted theoretically in the Tomonaga-Luttinger Liquid model. The observation of Luttinger Liquid behaviour demonstrates the outstanding nature of these one-dimensional molecular systems. In these devices the charging Coulomb energy of a single particle played a critical role in the overall device performance. This study can be used to understand the nature of dynamics of plasmons which are the charge carriers in a TLL system and how Coulomb interactions can be used to design highly tuneable systems for fabrication of single molecule devices. The incorporation of metal onto individual SWNT ropes does not alter its electronic properties significantly but the properties of the bundled metal incorporated SWNT ropes are altered. This study has found that under optimized conditions SWNTs might be a viable option for incorporation in nano electronics devices. Individual SWNT ropes promise better devices compared to SWNT mats and further work should be done on individual SWNTs.
Keywords: Carbon.; Nanotubes, Carbon content.; Nanotubes.; Laser ablation.